Modification of turbulence on floating solar farms in coastal waters - Olivera, Denise Samantha Jambalos (Nanyang Technological University, 2024)
With the push to move away from non-renewable sources of energy, the lack of viable renewable sources and land space have caused Singapore to utilise the surfaces of reservoirs for the installation of floating solar farms. Recently, there have been plans to test out these floating solar farms in the open sea environment to make further use of the water surface available to Singapore. Since these floating solar farms are large, its hydrodynamic effects need to be understood to quantify the possible environmental effects. This project investigates the effects of floating platforms on the hydrodynamic characteristics of the coastal environment, which include velocity profiles, turbulence characteristics, Reynolds stresses and turbulent kinetic energy. Experiments were carried out using Particle Image Velocimetry in a recirculating flume and the results were obtained and analysed using PIVlab and MATlab. The results were then used to calculate and plot graphs of the changes in suspended sediment transport. The results indicated an overall increase in the turbulence intensities, Reynolds stresses and turbulent kinetic energy. Suspended sediment calculations also showed an overall increase in the capacity. For most cases, the partial cover with the least coverage (70% open) had the most significant changes in turbulence characteristics and the suspended sediment capacity.